Ethical and Psychosocial Implications of Genomic Newborn Screening - Harvey L. Levy (MDPI AG, 2021)
The potential for genomic screening of the newborn, specifically adding genomic screening to current newborn screening (NBS), raises very significant ethical issues. Regardless of whether NBS of this type would include entire genomes or only the coding region of the genome (exome screening) or even sequencing specific genes, the ethical issues raised would be enormous. These issues include the limitations of bioinformatic interpretation of identified variants in terms of pathogenicity and accurate prognosis, the potential for substantial uncertainty about appropriate diagnosis, therapy, and follow-up, the possibility of much anxiety among providers and parents, the potential for unnecessary treatment and "medicalizing" normal children, the possibility of adding large medical costs for otherwise unnecessary follow-up and testing, the potential for negatively impacting medical and life insurance, and the almost impossible task of obtaining truly-informed consent. Moreover, the potentially-negative consequences of adding genomic sequencing to NBS might jeopardize all of NBS which has been and continues to be so beneficial for thousands of children and their families throughout the world.